DA’WAH SALAFI DI KALANGAN SELEBRITAS HIJRAH - Oki Setianad Dewi; Ahmad Khoirul Fata (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
Many Islamic movements have emerged with a different style from the mainstream. One of them is the Salafi movement. Although many parties reject Salafi preaching, not a few can also accept it, one of them is a group of artists who are growing their religious passion. They are known as hijra celebrities. This article discusses the process of acceptance of Salafi da'wah among hijra celebrities. This research is field research with a descriptive qualitative approach. The primary data of this study were obtained from in-depth interviews with preachers and celebrities who attended Salafi recitations. The research subjects were determined purposively after observing several Hijra artists. This research also utilizes various literature related to the Salafism theme and the phenomenon of Hijra celebrity. The results show that social media plays an important role in encouraging the development of the Hijra movement. Social media has connected Hijra celebrities with Salafi preachers. Some of the celebrities interviewed admitted that their interest in attending Salafi studies grew after listening to recitations through social media. Thus, Hijra celebrities are actively seeking and receiving Salafi preaching.